(untitled) (Revista Torreón Universitario, 2022)
The purpose of the research is the analysis of the factors that determine quality management at the Continuous and Postgraduate Education Unit (QMCPEU) of the Regional Multidisciplinary Faculty of Carazo, of the National Autonomous University of Nicaragua, Managua, from the perspective of the actors involved; and students, teaching staff and management teams, considering that institutions of higher education at the graduate level should establish a program of continuous improvement. The study involves the description of the context of quality management in higher education, the approach of the factors for quality management, the knowledge of the perception of quality management, through the triangulation of information between governing bodies, users, and teachers, in addition to the opinion of experts in the area of study. As for the methodology, this research is developed under a positivist paradigm with a quantitative approach, so the data provided by the key actors are described and analyzed. As a result, it was found that the QMCPEU faces limitations related to curricular improvement, human talent management, administrative and financial efficiency, the effectiveness of the teaching-learning process, provision of infrastructures, technological equipment, graduate monitoring processes, and especially the lack of a culture of service. Finally, the proposal of the management model for quality service culture "CLOSER" is presented, which has a humanistic approach to the organization oriented towards the user.